Probiotic and antifungal attributes of lactic acid bacteria isolates from naturally fermented Brazilian table olives - Simões, Luara (2022)
Research with fermented olives as a source of wild Lactic Acid Bacteria (LAB) strains with probiotic and biotechnological characteristics constitutes a promising field of work. The present study evaluated in vitro probiotic, antifungal, and antimycotoxigenic potential of LAB isolates from naturally fermented Brazilian table olives. Among fourteen LAB isolates, the Levilactobacillus brevis CCMA 1762, Lactiplantibacillus pentosus CCMA 1768, and Lacticaseibacillus paracasei subsp. paracasei CCMA 1770 showed potential probiotic and antifungal properties. The isolates showed resistance to pH 2.0 (survival ≥ 84.55), bile salts (survival ≥ 99.44), and gastrointestinal tract conditions (survival ≥ 57.84%); hydrophobic cell surface (≥27%); auto-aggregation (≥81.38%); coaggregation with Escherichia coli INCQS 00181 (≥33.97%) and Salmonella Enteritidis ATCC 564 (≥53.84%); adhesion to the epithelial cell line Caco-2 (≥5.04%); antimicrobial activity against the bacteria S. Enteritidis ATCC 564 (≥6 mm), Listeria monocytogenes ATCC 19117 (≥6 mm), Staphylococcus aureus ATCC 8702 (≥3 mm), and the fungi Penicillium nordicum MUM 08.16 (inhibition ≥ 64.8%). In addition, the strains showed the ability to adsorb the mycotoxins aflatoxin B1 (≥40%) and ochratoxin A (≥34%). These results indicate that LAB strains from naturally fermented Brazilian table olives are potentially probiotic and antifungal candidates that can be used for food biopreservation.